2011
DOI: 10.1038/modpathol.2010.191
|View full text |Cite
|
Sign up to set email alerts
|

Increased insulin-like growth factor-1 receptor mRNA expression predicts poor survival in immunophenotypes of early breast carcinoma

Abstract: The biology of breast carcinoma shows a great variation, reflected by the recent classification of phenotypes based on DNA microarrays or immunohistochemistry. The aim of this study was to determine the prevalence of insulin-like growth factor-1 receptor (IGF1R) in breast carcinoma subtypes and the impact on the outcome. We studied 197 consecutive breast carcinoma patients in stage I-II treated conservatively. Phenotypes were assessed on the basis of the expressions of ER/PR, HER2, Ki67, p53, Bcl2, CK5/6 and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 41 publications
(63 reference statements)
1
33
0
2
Order By: Relevance
“…IGF1R expression in ER(+) tumors is strongly related to a favorable disease-free survival and breast cancer specific survival, but to a shorter survival in triple negative carcinoma [35]. Increased IGF1R mRNA levels according to intrinsic subtypes were found in 53% of Luminal A, 24% of Luminal B, 13% of HER2 and 10% of triple negative tumors, respectively [36]. On the basis of research on insulin/ IGF-1R, a new approach to individualized cancer therapy termed metabolo-genomics is proposed which incorporates features of both cell metabolism and gene profiling.…”
Section: Discussionmentioning
confidence: 90%
“…IGF1R expression in ER(+) tumors is strongly related to a favorable disease-free survival and breast cancer specific survival, but to a shorter survival in triple negative carcinoma [35]. Increased IGF1R mRNA levels according to intrinsic subtypes were found in 53% of Luminal A, 24% of Luminal B, 13% of HER2 and 10% of triple negative tumors, respectively [36]. On the basis of research on insulin/ IGF-1R, a new approach to individualized cancer therapy termed metabolo-genomics is proposed which incorporates features of both cell metabolism and gene profiling.…”
Section: Discussionmentioning
confidence: 90%
“…IGF signaling has been shown to be a direct therapeutic target in TNBC (Creighton et al 2008, Bhargava et al 2011, Davison et al 2011. Briefly, IGF1R was shown to be expressed and activated by phosphorylation in TNBC (Lerma et al 2007, Law et al 2008, high IGF1R mRNA expression leads to poorer overall survival in basal/triple-negative groups (Peiro et al 2011) and rare high-level amplification of IGF1R has been detected in some basal-like breast cancers (Adelaide et al 2007). Collectively, these studies highlight that IGF1R is an oncogenic driver and therapeutic target in TNBC.…”
Section: Triple-negative Breast Cancersmentioning
confidence: 97%
“…However, its prognostic value is controversial depending on the sites of carcinoma [4,17,18,19,20,21,22]. Many reports suggested that IGF1R expression correlated with poor survival in breast cancer [18,23,24]. In contrast, Fu et al [23] described that IGF1R mRNA expression was significantly higher in patients with favorable clinicopathologic parameters.…”
Section: Discussionmentioning
confidence: 92%
“…Overexpression of IGF1R has been reported in a wide variety of human carcinomas, including breast cancer, gallbladder carcinoma, esophageal squamous cell carcinoma, prostate cancer, renal cell carcinoma, and colorectal carcinoma. However, its prognostic value is controversial depending on the sites of carcinoma [4,17,18,19,20,21,22]. Many reports suggested that IGF1R expression correlated with poor survival in breast cancer [18,23,24].…”
Section: Discussionmentioning
confidence: 99%